Peer effects, social multipliers and migrants at school: an international comparison - Horst Entorf; Martina Lauk (Technische Universität Darmstadt, Department of Law and Economics, 2006)
This article analyses the school performance of migrants dependent on peer groups in different international schooling environments. Using data from the international OECD PISA test, we consider social interaction within and between groups of natives and migrants. Results based on social multipliers (Glaeser et al. 2000, 2003) suggest that both native-tonative and migrant-to-migrant peer effects are higher in ability-differencing school systems than in comprehensive schools. Thus, non-comprehensive school systems seem to magnify the prevailing educational inequality between students with a low parental socioeconomic migration background and children from more privileged families.
Keywords: I21; 330; Peer effects; migration; education; social multipliers; school systems; parental socioeconomic background